Contemporary phantasmagorias - Ainá Rocha (Journal of Science and Technology of the Arts, 2022)
The following essay intends an approach that comprises a combination of aesthetics, history and philosophy to reproduce the perception of certain elements of image contradictions in contemporary times. It discusses the concepts of phantasmagoria and apparition regarding technical and memory images and will be presented contemporary examples that contribute to the understanding of those types of images as irrefutable components in the fields of current ontology and epistemology.